Utopia as method: a response to education in crisis?. (14th January 2022) - Van Dermijnsbrugge, Elke; Chatelier, Stephen
ABSTRACT: Claims of crisis in education are not new though their orientation has changed over time. This paper is concerned with the contemporary discourse surrounding an apparent global learning crisis, examining the dominant logics through which education and its concomitant crises are imagined and operationalized. In this conceptual essay, we take "crisis" as representing both challenges faced by society and as an opportunity to interrupt the current order. We suggest that a key crisis facing education currently is not a learning crisis, but the dominant evidence-based approach and "what works" logic. In response, we argue for utilizing Levitas' utopia as method as a way for educational researchers and practitioners to engage in imagining alternative futures. The method involves excavation of conditions that have resulted in the current moment, critical questioning of being for both humans and the institutions we construct, and imagining alternative ways of being and doing education. We illustrate briefly how the method can be used in applying it to an analysis of the OECD's Global Competency Framework. This method is not presented as a solution, but as a crisis response that is imaginative and attempts to create possibilities and spaces of hope.